Supplier Optimization Strategy, Risk Strategy and Enterprise Supply Chain Performance of SMEs: A Study in Bamenda City - Nsawir, Jude Bonglav; Jumbo, Urie Eleazar; Chiatii, Elizabeth Ankiambom (Finance & Economics Review, 2024)
Purpose: Small and Medium Enterprises (SMEs) in Bamenda City are integral to the region's economic development, contributing significantly to employment, innovation, and economic growth. Supply chain management involves the coordination and optimization of activities related to sourcing, production, and delivery of products and services. The main objective of this study was to investigate the effects of supplier optimization strategy and risk strategy on the enterprise supply chain performance of SMES in Bamenda City. Methods: Data for this study was obtained with the help of a structured questionnaire. By combining both designs, the study can first describe the existing situation or relationships (descriptive), and then explore or test potential causes and effects (causal). The partial least square regression model was used to analyze the paper. Results: Results from partial least squares structural equation models (PLS-SEM) revealed a positive insignificant effect of supplier optimization strategy on supply chain performance. Risk strategy was also found to exert a positive effect on supply chain performance everything being equal. Implications: Although supplier optimization has a positive impact on supply chain performance, the effect is insignificant. This suggests that while the strategy is directionally sound, it may need to be enhanced or refined. Also, given the positive significant effect of the risk strategy on supply chain performance, organizations should continue to focus on and invest in risk management.